2011
DOI: 10.2147/ceg.s18585
|View full text |Cite
|
Sign up to set email alerts
|

Assessing patients’ satisfaction with anti-TNFα treatment in Crohn’s disease: qualitative steps of the development of a new questionnaire

Abstract: Purpose:To develop a self-administered questionnaire assessing patients’ satisfaction with treatments in Crohn’s disease for use in clinical research and epidemiological studies.Patients and methods:Semi-directive interviews (16) were conducted with patients with severe Crohn’s disease treated with anti-tumor necrosis factor alpha (anti-TNFα). Transcripts were analyzed and concepts related to satisfaction with treatment were extracted and organized into a model. Items were generated using patients’ words. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… 5 The SPACE-Q was developed following a rigorous methodology compatible with regulatory authorities’ standard requirements for patient-reported outcome instruments. 13 , 14 In this study, we found that the final version of the SPACE-Q demonstrated good psychometric properties, including good clinical and concurrent validity, good internal consistency and test–retest reliability, and good responsiveness.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“… 5 The SPACE-Q was developed following a rigorous methodology compatible with regulatory authorities’ standard requirements for patient-reported outcome instruments. 13 , 14 In this study, we found that the final version of the SPACE-Q demonstrated good psychometric properties, including good clinical and concurrent validity, good internal consistency and test–retest reliability, and good responsiveness.…”
Section: Discussionmentioning
confidence: 61%
“…The SPACE-Q was recently developed to evaluate satisfaction with anti-TNF treatments of patients with severe Crohn’s disease. 13 In this multicenter, longitudinal, noninterventional study, we have shown that this questionnaire is well accepted by patients with severe Crohn’s disease and is a valid, reliable, and responsive tool to assess their satisfaction with respect to the specificities of anti-TNF treatment.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations